10 Why the Archaeology of Political Ecology Matters. Issue 1 (2nd July 2018) - Ashmore, Wendy
ABSTRACT: Archaeology and anthropology generally share with geography an interest in the relationship of humans to their environments. This relationship involves material exchanges but also draws from social relations as well as political, symbolic, and religious practices. Thus, while climate and natural resources shape human biology and culture over time, human culture and politics have reciprocal impacts on the environment, cross‐culturally and across time. This has become the realm of political ecology. Well‐known cases of such impact in historical and modern contexts highlight contrasts between views of Thomas Malthus and Esther Boserup on connections between population size and food supplies, or between the spread of infectious diseases and socioeconomic standing. More succinctly, Paul Robbins (2012, 14) asserts: "political ecology represents an explicit alternative to 'apolitical' ecology." Contributors to this volume raise thought provoking issues in political ecology from an archeological perspective, simultaneously reporting concrete findings and inspiring new lines of research in richly varied cultural and environmental contexts. This chapter discusses insights and challenges in the collective contributions, presented via three themes: (1) inequality in access to landscape resources; (2) multiplicity of time frames, from events to long‐term; and (3) the potential characteristics of "nature" in political ecological dynamics. The chapter closes with summary thoughts on why the archaeology of political ecology matters.